PERANAN KURIKULUM 2013 DALAM MENGEKSPLORASI KOMPETENSI SISWA - Amanaturrakhmah, Isna (Jurnal Tawadhu, 2021)
This study aims to describe teachers' perceptions of the 2013 curriculum and explore student competencies in 2015-2020 as long as the 2013 curriculum is applied. The method used in this research is library research. The data source comes from the studies that have been done. Data collection is done by finding sources and constructing from various sources. Testing the validity of the data was carried out using a credibility test, namely time triangulation, for data validity regarding the development of the 2013 curriculum implications during 2015-2020. After that, the data were analyzed using a qualitative descriptive method. The results showed that teachers positively perceived that the 2013 curriculum had an ideal concept. Meanwhile, the various obstacles teachers face are the impact of the government's lack of readiness in developing the 2013 curriculum and the lack of openness of education practitioners in accepting change. Over time, the implementation of the 2013 curriculum in education in Indonesia is improving and positively influences student achievement. The learning outcomes obtained are not only numerical values. In addition to cognitive development, students also gain growth in cognitive and psychomotor aspects.